Effect of novel bright image enhanced endoscopy using blue laser imaging (BLI) - Kazuhiro Kaneko; Yasuhiro Oono; Tomonori Yano; Hiroaki Ikematsu; Tomoyuki Odagaki; Yusuke Yoda; Atsushi Yagishita; Akihiro Sato; Shogo Nomura (Endoscopy International Open, 2014)
Background and study aims: The novel method of image-enhanced endoscopy (IEE) named blue laser imaging (BLI) can enhance the contrast of surface vessels using lasers for light illumination. BLI has two IEE modes: high contrast mode (BLI-contrast) for use with magnification, and bright mode (BLI-bright), which achieves a brighter image than BLI-contrast and yet maintains the enhanced visualization of vascular contrast that is expected for the detection of tumors from a far field of view. The aim of this study is to clarify the effect of BLI-bright with a far field of view compared to BLI-contrast and commonly available narrow-band imaging (NBI). Patients and methods: Patients with neoplasia, including early cancer in the pharynx, esophagus, stomach, or colorectum, were recruited and underwent tandem endoscopy with BLI and NBI systems. Six sets of images of the lesions were captured with a changing observable distance from 3 to 40 mm. Individual sets of images taken from various observable distances were assessed for visibility among BLI-bright, BLI-contrast, and NBI modes. The brightness and contrast of these images were also analyzed quantitatively. Results: Of 51 patients, 39 were assessed. Image analysis indicated that only BLI-bright maintained adequate brightness and contrast up to 40 mm and had significantly longer observable distances compared to the other methods. Furthermore, BLI-bright enhanced the visualization of serious lesions infiltrating into deeper layers, such as esophageal lamina propria or gastric submucosal cancers. Conclusions: BLI-bright will be a helpful tool for the far-field view with IEE in organs with wider internal spaces such as the stomach.